HUBUNGAN ANTARA DUKUNGAN SOSIAL SUAMI DENGAN STRES PADA PENDERITA KANKER PAYUDARA DI DEPARTEMEN BEDAH RSUPN CIPTO MANGUNKUSUMO JAKARTA PUSAT - Shanty Sudarji (Universitas Bunda Mulia, 2011)
Development of the modern era of increasingly broad impacts on the various sides of human life, a change not only affects the thinking and technology, but also to the tendency of the illness. Cancer and various accompanying events can be stressful for the patient. Therefore needed in order to support the patient, the patient’s husband helped her recovery and the patient can survive longer. Stress is a presumption of the individual to a source or a situation which was considered to give the pressure, excitement and a certain burden, both physically and psychologically that is not commensurate with her that she perceived as a threat to the welfare of one's life. Social support assistance provided by the husband is the husband as the people closest to the patient. Breast cancer is a disease caused by the growth of abnormal breast cells, which is the process of malignancy in the breast that often causes death in the group of women sufferers.Independent variables in this study is social support of the husband, the dependent variable is the stress in patients with breast cancer. The study population were women with breast cancer at the Department of Surgery Cipto Mangunkusumo Central Jakarta. Purposive sampling method to sample and try out using unused. Scale of social support and stress scale each consisting of 52 items. Methods of analysis using Pearson Product Moment Correlation. Based on research results found that there is a relationship between social support dan stress.Keywords: social support, stress, breast cancer patient